1998
DOI: 10.1016/s0168-6445(98)00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial desulfonation

Abstract: Organosulfonates are widespread compounds, be they natural products of low or high molecular weight, or xenobiotics. Many commonly found compounds are subject to desulfonation, even if it is not certain whether all the corresponding enzymes are widely expressed in nature. Sulfonates require transport systems to cross the cell membrane, but few physiological data and no biochemical data on this topic are available, though the sequences of some of the appropriate genes are known. Desulfonative enzymes in aerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 122 publications
(232 reference statements)
2
79
0
Order By: Relevance
“…The microbial degradation of aromatic sulfonic acids has mainly been studied using simple benzenesulfonates and naphthalenesulfonates as model compounds. These studies demonstrated that sulfonated substrates are in most cases initially desulfonated by the action of ring-hydroxylating dioxygenases to the corresponding diols (Brilon et al, 1981;Cook et al, 1999;Nörtemann et al, 1986;Ohe et al, 1990;Thurnheer et al, 1990;Wittich et al, 1988). In contrast, it has been found that 4-aminobenzenesulfonate (sulfanilate) was initially deaminated by a co-culture of Hydrogenophaga intermedia S1 and Agrobacterium radiobacter S2 to 4-sulfocatechol (Feigel & Knackmuss, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial degradation of aromatic sulfonic acids has mainly been studied using simple benzenesulfonates and naphthalenesulfonates as model compounds. These studies demonstrated that sulfonated substrates are in most cases initially desulfonated by the action of ring-hydroxylating dioxygenases to the corresponding diols (Brilon et al, 1981;Cook et al, 1999;Nörtemann et al, 1986;Ohe et al, 1990;Thurnheer et al, 1990;Wittich et al, 1988). In contrast, it has been found that 4-aminobenzenesulfonate (sulfanilate) was initially deaminated by a co-culture of Hydrogenophaga intermedia S1 and Agrobacterium radiobacter S2 to 4-sulfocatechol (Feigel & Knackmuss, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This is perhaps not surprising, given the large percentage of sulfonates in soil and sediment sulfur, and the facts that humic materials are sulfonates and subject to rapid¯ux in soil (reviewed in Cook et al 1998). What is less obvious in these reports is the frequency with which pure cultures are not obtained (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of organosulfonates as carbon sources for growth is characterised by organisms with narrow substrate ranges (one to three sulfonated compounds) (Cook et al 1998), though exceptions are known (see Haug et al 1991) and some naphthalenedisulfonates are biodegradable (e.g. Wittich et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…[46] Anaerobic desulfonation has been demonstrated during fermentation, resulting in the loss of SO 3 as sulfide or thiosulfate. [47] Although differential accumulation of PO 4 -riboside cannot be discounted, it is unlikely that high PO 4 -riboside concentrations in animal tissues are the result of direct ingestion, as their diet is composed of ∼79% SO 3 -riboside from E. radiata, (Table A4). PO 4 -riboside has been found previously as the sole arsenoriboside in the digestive gland of the western rock lobster Panulirus cygnus, and in mussels.…”
Section: Possible Mechanisms For the Metabolism Of Arsenoribosides Anmentioning
confidence: 99%